“USE OF METAPHOR AND FRAMING AS PRAGMATIC STRATEGIES IN ENGLISH AND UZBEK POLITICAL DISCOURSE” (ZAMONAVIY TARAQQIYOT VA FAN: 21-ASR YONDASHUVLARI, 2025)
This work examines the use of metaphor and framing as pragmatic strategies in English and Uzbek political discourse. It focuses on how metaphorical expressions guide interpretation and shape meaning implicitly rather than explicitly. The purpose of the analysis is to identify how different metaphoric frames are employed to influence audience understanding and to compare their pragmatic functions across the two languages. By analyzing selected English and Uzbek texts, the study aims to show how metaphor and framing operate as tools of persuasion and meaning management in political communication.